The Maintenance Process Improvement of Radiological Health Equipment, by Utilizing Internet of Things (IoT) - Z J Azra, M Dachyar (International Journal of Advanced Science and Technology, 2020)
Hospitals must ensure that their medical devices are safe, accurate, reliable, and comply with a particular level of performance. Taking one private hospital in Indonesia as a research object, in radiology, the conventional X-ray and Panoramic devices are the highest usage equipment. Proper maintenance should be done to avoid any possible breakdown. The process of maintaining medical equipment adopted by the hospital is currently 37,41% consist of manual administration (paperwork) and only 54,04% of actual inspection and maintenance activities. This research aims to improve the maintenance process of conventional X-rays and panoramic devices, by utilizing the Internet of Things (IoT). Business Process Reengineering (BPR) is used to rectify the health equipment maintenance process. The information system is proposed to the maintenance process using Data Flow Diagram (DFD). This research recommends four maintenance process improvement options, where the highest time efficiency is 56.25%, which is generated by the selection improvement “intervention of Computerized Maintenance Management System (CMMS) software, integrated QR Code and radiofrequency Identification (RFID) tags, and condition-based monitoring technology/sensor”.